Stylistic Application of Attributive Collocations in Contemporary English - Витоните, И. (Kalbotyra, 1963)
Contemporary English is characteristic of manymember attributive collocations, such as (a) come-to-the-battle (sort of a note), (a) cost-of-living (index), (a) dacron-and-cotton (blouse), (a) do-it-yourself (manual), (a) “Let’s-disarm-within-fouryears” (speech) etc. The studied material confirmed that in a great majority of cases attributive collocations of the type are used for special stylistic purposes, i. e. they perform a number of functions according to the aim of statement or declaration and have a special stylistic and emotional (expressive) colouring. The range of application of the studied collocations in different styles of speech may be grouped as follows: the greatest majority of them is used in the newspaper style (including here the style of the language of popular magazines); attributive collocations used in fiction are met less frequently (depending upon the style of separate authors); in the style of scientific literature the attributes of the studied type are met to a far smaller extent. Attributive collocations perform the following functions according to the purpose of statement: A) The function of short, compact nomination of the attribute of an object or thing. This functions is a peculiarity of the style of newspapers and popular magazines. B) The second characteristic function of attributive collocations is the function of the main predication about the nouns they modify. This function accounts for a wide use of attributive collocations in a) newspaper headlines and b) advertisments. C) The function of short, compact nomination is closely connected with the function of termination. The studied material shows that this function is charakteristic of attributive collocations in: a) the special-scientific and b) the newspaper functional styles. D) One of the characteristic functions of attributive collocations is the function of picturesqueness. This function is peculiar even to some social-political, financial and scientific terms. According to some lexical, morphological and syntactical features a part of the studied attributes might be classed as belonging to the colloquial style. Scientific terms, however, can’t be looked upon as colloquial lexical units. The studied material showed that attributive collocations may have a colloquial stylistic colouring and, thus, comprise humoristic, ironical, declarative, pathetic, emotional etc. character. The colloquial stylistic colouring and particular emotional character is met most often with the nonce collocations of the type. Substituting the studied prepositional collocations by attributes in postposition, the latter lose a great deal of their above-mentioned stylistical value